Sistem dan Kebijakan Pemerintah Terhadap Pendidikan Islam Pada Era Reformasi - Tiara Salwadila (LP4MK STKIP PGRI Lubuklinggau, 2021)
The Purpose of this research were to discuss the system and policies of the Indonesian Goverment in this reform era in the part of education, especially in Islamic Eduction. This study used qualitative methods. The data collected in this study are secondary data. The Islamic education system in the reform era was much better tahn colonial system until the new order, because islamic eduction policies in Indonesia such as madrasah were better. The policies are in the form of incom policy on education budget, policy on strengthening Islamic education as anational education system, polycy on teh 9 year compulsory education program, competency-based cuririculum and education unit level curriculum, and policies to change the nature of madrasah to become general.